Effect of Sparse Doping in Barriers on the Energy Structure of Center-Delta-Doped QW (2019)
Effect of sparse (presumably background) shallow donor impurity on the energy structure of SiGe/Si quantum well structure delta-doped to the center of the well is studied numerically. The method includes calculation of impurity binding energy. The proposed nanostructure configuration can be used to create tunable optical devices in THz frequency region. © 2019 IEEE.